Տարածքային կառավարման համակարգը որպես ՀՀ ռազմական անվտանգության ապահովման սուբյեկտ - Հայկ Անտոնյան (ՀՀ ԳԱԱ հրատ.)
Понимание сущности военной безопасности, ее структурно-контекстуальных и деятельностных аспектов, а также практические решения вопросов, связанных с военной безопасностью, невозможно реализовать, не понимая природы его субъектов в этой сфере. Understanding the nature of military security, its structural-contextual and activity-related aspects as well as practical solutions for issues related to military security cannot be implemented without understanding the nature of its subjects in this sphere.
Keywords: Social Sciences; Economic Theory; Military Science